Artificial Intelligence–Based Screening for Mycobacteria in Whole-Slide Images of Tissue Samples. Issue 1 (2nd February 2021) - Pantanowitz, Liron; Wu, Uno; Seigh, Lindsey; LoPresti, Edmund; Yeh, Fang-Cheng; Salgia, Payal; Michelow, Pamela; Hazelhurst, Scott; Chen, Wei-Yu; Hartman, Douglas; Yeh, Chao-Yuan
Abstract: Objectives: This study aimed to develop and validate a deep learning algorithm to screen digitized acid fast–stained (AFS) slides for mycobacteria within tissue sections. Methods: A total of 441 whole-slide images (WSIs) of AFS tissue material were used to develop a deep learning algorithm. Regions of interest with possible acid-fast bacilli (AFBs) were displayed in a web-based gallery format alongside corresponding WSIs for pathologist review. Artificial intelligence (AI)–assisted analysis of another 138 AFS slides was compared to manual light microscopy and WSI evaluation without AI support. Results: Algorithm performance showed an area under the curve of 0.960 at the image patch level. More AI-assisted reviews identified AFBs than manual microscopy or WSI examination ( P < .001). Sensitivity, negative predictive value, and accuracy were highest for AI-assisted reviews. AI-assisted reviews also had the highest rate of matching the original sign-out diagnosis, were less time-consuming, and were much easier for pathologists to perform ( P < .001). Conclusions: This study reports the successful development and clinical validation of an AI-based digital pathology system to screen for AFBs in anatomic pathology material. AI assistance proved to be more sensitive and accurate, took pathologists less time to screen cases, and was easier to use than either manual microscopy or viewing WSIs.